Do We Need Big Banks? Evidence on Performance, Strategy and Market Discipline - Demirgüç-Kunt, Asli; Huizinga, Harry (2012)
For an international sample of banks, the authors construct measures of a bank's absolute size and its systemic size defined as size relative to the national economy. They examine how a bank's risk and return, its activity mix and funding strategy, and the extent to which it faces market discipline depend on both size measures. Although absolute size presents banks with a trade-off between risk and return, systemic size is an unmitigated bad, reducing return without a reduction in risk. Despite too-big-to-fail subsidies, the analysis finds that systemically large banks are subject to greater market discipline as evidenced by a higher sensitivity of their funding costs to risk proxies, suggesting that they are often too big to save. The finding that a bank's interest cost tends to rise with its systemic size can also in part explain why a bank's rate of return on assets tends to decline with systemic size. Overall, the results cast doubt on the need to have systemically large banks. Bank growth has not been in the interest of bank shareholders in small countries, and it is not clear whether those in larger countries have benefited. Although market discipline through increasing funding costs should keep systemic size in check, clearly it has not been effective in preventing the emergence of such banks in the first place. Inadequate corporate governance structures at banks seem to have enabled managers to pursue high-growth strategies at the expense of shareholders, providing support for greater government regulation.